TINDAK PIDANA KHALWAT DI NANGGROE ACEH DARUSSALAM DALAM PERPEKTIF HUKUM PIDANA INDONESIA - Idaliyah, Siti (UIN Sunan Kalijaga Yogyakarta, 2014)
Aceh is one of the regions in Indonesia which have the particularity in thefield of law, it can be seen from the Law No. 11/2006 on the Governingof Aceh. Therefore, the government of Aceh set Qanun as the rule of law inforce. Among the qanun are Qanun No. 14 of 2003 on action seclusion/nasty. Viewed from the perspective of Indonesian Criminal Code, thekhalwat is including violations seclusion immoral acts, as stated in Article532-536 of the Indonesian Criminal Code. Between Qanun seclusionwith the Criminal Code there are similarities in terms of the purpose ofpunishment. The general objective of both of this regulation is to providea deterrent punishment for the perpetrator and a lesson for others not to dothe same. However, there are differences between the provisions of Qanunseclusion with wanton violation of the Criminal Code, namely in terms ofthe type of punishment for violators of the offense and the law enforcement